Publipreneur based Language Learning (PBLL) as Thematic Approach in Teaching English for Creative Industry - Zalzulifa, Zalzulifa; Nasruddin, Nasruddin; Rabernir, Rabernir (Riviera Publishing, 2023)
The purpose of this study is to evaluate the effectiveness of Publipreneur Based Language Learning (PBLL) as a thematic approach in teaching English, particularly for the creative industry. In finding the right way to design English materials for the creative industry, researchers conducted a student needs assessment through questionnaires, interviews, and classroom observation (simulation) in the learning process. The research questions were answered through eight items of respondents' understanding, namely: 1) Lecturers' perception of the creative industry; 2) Lecturers' institutional awareness; 3) The role of students in learning activities; 4) The role of lecturers in the learning process; 5) Evaluation in the learning process; 6) Difficulties in designing English materials; 7) Solutions in problem solving; 8) Designing PBLL Materials for Creative Industries. The findings of this study include three main points. First, to meet the needs, the design of English learning materials should be formulated according to the competency level of the Indonesian national qualification framework approach. Second, to meet the needs of the industry, the design of English learning materials should be able to encourage them in performing various technical skills and competencies needed by the industry. Third, to improve one's proficiency in understanding EOP materials, the design of English learning materials can elaborate Kathelen Graven's model with its modification by prioritizing concept actualization after content conceptualization.